GASTON BACHELARD AND PIERRE DUHEM: EPISTEMOLOGICAL DISCONTINUITY AND CONTINUITY - Velanes, David (Revista Inter-Legere, 2018)
This article aims to clarify the theme of continuity and epistemological discontinuity from Pierre Duhem (1861-1916) and Gaston Bachelard (1884-1962), both French thinkers. The first author has a continuum view on the development of sciences, in which the progress of scientific knowledge would occur from continuous repairs on a theoretical system that evolves gradually. Gaston Bachelard, on the other hand, defends the thesis of the epistemological rupture, according to which he thinks the evolution of the sciences through his interregnums and reorganizations. Knowledge moves through rectifications of knowledge that are updated in the light of new experiences, without a cumulative process of ideas occurring. It is intended in this work to clarify the Bachelardian view on epistemological discontinuity as opposed to Duhemian thought. Keywords: Continuity. Discontinuity. Epistemology. Duhem. Bachelard.